Genome-Wide Identification of the Early Flowering 4 (ELF4) Gene Family in Cotton and Silent GhELF4-1 and GhEFL3-6 Decreased Cotton Stress Resistance - Tian, Miaomiao; Wu, Aimin; Zhang, Meng; Zhang, Jingjing; Wei, Hengling; Yang, Xu; Ma, Liang; Lu, Jianhua; Fu, Xiaokang; Wang, Hantao; Yu, Shuxun (Frontiers in Genetics, 2021)
The EARLY FLOWERING 4 (ELF4) family plays a variety of roles in plant physiological activities and development. ELF4 participates in the plant biological clock's regulation process, photoperiod, hypocotyl elongation, and flowering time. However, the function of the ELF4s gene is barely known in cotton. In this study, 11, 12, 21, and 22 ELF4 genes were identified from the genomes of Gossypium arboreum, G. raimondii, G. hirsutum, and G. barbadense, respectively. This ELF4s gene was classified into four subfamilies. Members from the same subfamilies showed relatively well-conserved gene structures, motifs, and protein domains. The results of gene chromosome location and gene duplication revealed that segmental duplication mainly promotes gene expansion, and the Ka/Ks values indicated that the ELF4 gene family has undergone purification selection during long-term evolution. Transcriptomic data and spatio-temporal expression patterns showed that GhELF4 genes are mainly related to flower, leaf and fiber development. The GhELF4s gene was analyzed for cis-acting elements and subjected to ABA and light treatment. The GhELF4s gene may be involved in the regulation of ABA or light pathways. Silencing of GhELF4-1 and GhEFL3-6 found that pYL-156-GhEFL3-6 and pYL-156-GhELF4-1 were significantly adjusted the height of cotton seedlings. And the resistance of cotton is reduced. The identification and functional analysis of GhELF4s gene in cotton may provide more candidate genes for genetic modification.